The exposome : a new paradigm for the environment and health - Miller, Gary W (Amsterdam : Academic Press, 2020)
The Exposome: A New Paradigm for the Environment and Health, Second Edition, is a thoroughly expanded and updated edition of The Exposome: A Primer, the first book dedicated to the topic. This new release outlines the purpose and scope of this emerging field of study, its practical applications, and how it complements a broad range of disciplines. The book contains sections on -omics-based technologies, newer detection methods, managing and integrating exposome data (including maps, models, computation and systems biology), and more. Both students and scientists in toxicology, environmental health, epidemiology and public health will benefit from this rigorous, yet readable, overview. This updated edition includes a more in-depth examination of the exposome, including full references, further reading and thought questions.
Keywords: Environmentally induced diseases. -- Epidemiology. -- adverse effects